An Epistemological Conception of Safe Spaces. (4th May 2021) - Anderson, Derek
ABSTRACT: The debate over safe spaces has traditionally been cast as a conflict between competing goals. On the one hand we have epistemic goals such as the pursuit of truth and the free exchange of ideas. On the other we have social, political, and ethical goals centered on protecting marginalized students from emotional and psychological trauma. Even proponents of safe space initiatives will often distinguish them from brave spaces, where brave spaces aim at truth as opposed to safety. Using concepts drawn from recent literature in social epistemology, this essay reframes the debate by developing a new epistemological conception of safe spaces. On this conception, the purpose of safe space initiatives is to safeguard marginalized students and colleagues against epistemic oppression and epistemic injustice and to promote recognition of situated knowledge, thereby promoting the pursuit of truth and the free exchange of ideas. These goals demonstrably align with the practices employed within traditional safe space initiatives, but also suggest new directives for creating and sustaining safe spaces that are explicitly aimed at combatting the effects of epistemic oppression. I show how this conception helps to defuse some of the traditional objections to creating safe spaces within academic settings.